Seedling growth Acacia farnesiana (L.) Willd on substrates containing different organic materials - Gonçalves, Elzimar de Oliveira; Petri, Gabrieli Moschen; Caçador, Douglas Almeida; Caldeira, Marcos Vinicius Winckler; Delarmelina, William Macedo (Revista Ecologia e Nutrição Florestal - ENFLO, 2014)
The search for forest products and services there is quality seedlings, an important factor in the success of forest plantations. In seedling production quality, an important aspect is the substrate used, as these need to have physical and chemical conditions suitable for plants. In this context, some organic materials have been used in substrate mixtures for the production the seedlings, for conferring improvements. The objective of this study was to test different proportions of organic materials such as chicken manure, ox manure and compost commercial production of seedlings of Acacia farnesiana (L.) Willd. However 11 treatments were defined, and were arranged in a complete randomized block design with three replications. At the end of 120 days after planting, the seedlings were evaluated as to the characteristics, height, dry weight of root, shoot and total, and quality index Dickson. After the analysis, it was concluded that best seedlings of Acacia farnesiana (L.) Willd is obtained by adding at least 20% chicken manure and cattle manure 40%, based on total dry mass.